Do Job Networks Disadvantage Women? Evidence from a Recruitment Experiment in Malawi - Beaman, Lori; Keleher, Niall; Magruder, Jeremy (Journal of Labor Economics, 2018)
We use a field experiment to show that referral-based hiring has the potential to disadvantage qualified women, highlighting another potential channel behind gender disparities in the labor market. Through a recruitment drive for a firm in Malawi, we look at men’s and women’s referral choices under different incentives and constraints. We find that men systematically refer few women, despite being able to refer qualified women when explicitly asked for female candidates. Performance pay also did not alter men’s tendencies to refer men. In addition, women did not refer enough high-quality women to offset men’s behavior.